Recommendations for detection and rapid management of carbapenemase-producing Enterobacterales outbreaks. Issue 3 (September 2020) - Puleston, R.; Brown, C.S.; Patel, B.; Fry, C.; Singleton, S.; Robotham, J.V.; Freeman, R.
Summary: There is large heterogeneity in approaches to tackling nosocomial outbreaks caused by carbapenemase-producing Enterobacterales (CPE), however there is limited guidance on how to approach their management. Rapid and robust infection prevention and control interventions can be effective in preventing and reducing the impact of outbreaks in healthcare environments. We present a stepwise approach to aspects of CPE outbreak management, including the development of an action plan, engagement and communication with key stakeholders, developing a dynamic risk assessment, and staff education. These can provide a blueprint for organisations to create templates and checklists to inform their own outbreak response.